Color‐Tunable Multifunctional Excited‐State Intramolecular Proton Transfer Emitter: Stimulated Emission of a Single Dye. Issue 44 (15th June 2022) - Durko‐Maciag, Martyna; Jacquemin, Denis; Ulrich, Gilles; Massue, Julien; Mysliwiec, Jaroslaw
Abstract: The excited‐state intramolecular proton transfer chromophores were regarded as good materials for laser action generation due to their inherent four‐level photocycle. The excitation‐dependent properties of these compounds enable light amplification from two distinct forms: both enol and keto, making it possible to obtain dual fluorescence emission. Herein, we report that a third option is possible for the first time stimulated emission was realized with a deprotonated ESIPT molecule based on a novel rigidified 2‐(2'‐hydroxyphenyl)benzothiazole derivative, triggering the possibility to fabricate real‐time tunable active material. Through the rational engineering of the ratio of each emissive species, a red‐green‐blue device was fabricated with the possibility of white light generation. The degenerated two‐wave mixing setup was applied to construct a continuously tunable distributed feedback laser. Abstract : A single 2‐(2'‐hydroxyphenyl)benzothiazole derivative is capable of precisely tunable triple‐emission, covering the whole visible spectrum (red‐green‐blue). Excited‐state intramolecular proton transfer (ESIPT) phenomenon was utilized to fabricate multifunctional active material for lasing action both in solutions and in thin polymeric films. For the first time, light amplification in deprotonated ESIPT species was observed, enabling real‐time shifting of the stimulated emission by almost 100 nm (from orange to green).